World history & geography - Spielvogel, Jackson J. (McGraw-Hill networks, 2014)
Chapter 1: The Rise of Civilization, Prehistory -- Chapter 2: The Spread of Civilization -- Chapter 3: Early Empires in the Ancient Near East -- Chapter 4: The Ancient Greeks -- Chapter 5: India's First Empires -- Chapter 6: The First Chinese Empires -- Chapter 7: The Romans -- Chapter 8: The Byzantine Empire and Emerging Europe -- Chapter 9: Islam and the Arab Empire -- Chapter 10: Medieval Kingdoms in Europe -- Chapter 11: Civilizations of East Asia -- Chapter 12: Crusades and Culture in the Middle Ages -- Chapter 13: Kingdoms and States of Medieval Africa -- Chapter 14: Pre-Columbian America -- Chapter 15: The Renaissance in Europe -- Chapter 16: The Reformation in Europe -- Chapter 17: The Age of Exploration -- Chapter 18: Conflict and Absolutism in Europe -- Chapter 19: The Muslim Empires -- Chapter 20: The East Asian World -- Chapter 21: The Enlightenment and Revolutions -- Chapter 22: The French Revolution and Napoleon -- Chapter 23: Industrialization and Nationalism -- Chapter 24: Mass Society and Democracy -- Chapter 25: The Reach of Imperialism -- Chapter 26: Challenge and Transition in East Asia -- Chapter 27: World War I and the Russian Revolution -- Chapter 28: The West Between the War -- Chapter 29: Nationalism Around the World -- Chapter 30: World War II and the Holocaust -- Chapter 31: The Cold War -- Chapter 32: Independence and Nationalism in the Developing World -- Chapter 33: Life During the Cold War -- Chapter 34: A New Era Begin -- Chapter 35: Contemporary Global Issues.